2021
DOI: 10.3390/electrochem2020023
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Effect of Zn Doping on Stability of Cobalt-Free P2-Na0.60Fe0.5Mn0.5O2 Cathode for Sodium Ion Batteries

Abstract: In this work, we report a sol-gel synthesis-based Zn-doped Na0.6Fe0.5Mn0.5O2 (NFM) cathode and understand the effect of Zn doping on the crystal structure and electrochemical performances such as discharge capacity and rate capability. Detailed X-Ray diffraction (XRD) pattern analysis indicated a decrease in the Na-layer thickness with Zn doping. Small amount of Zn2+ dopant (i.e., 2 at.%) slightly improved cycling stability, reversibility, and rate performances at higher discharge current rates. For example, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…Crystallographic evaluations of the sol-gel synthesized P2-type Na 0.67 Fe 0.5 Mn 0.5 O 2 were performed using the XRD patterns, shown in Figure 3a. The patterns showed that the NFM powder samples had a hexagonal, layered structure with a P63/mmc space group, as reported in our previous paper [32,33]. The morphology of the powder samples was observed using an ultra-high-resolution Field Emission Scanning Electron Microscope (FE-SEM) Hitachi SU7000.…”
Section: Materials Characterizationsupporting
confidence: 71%
“…Crystallographic evaluations of the sol-gel synthesized P2-type Na 0.67 Fe 0.5 Mn 0.5 O 2 were performed using the XRD patterns, shown in Figure 3a. The patterns showed that the NFM powder samples had a hexagonal, layered structure with a P63/mmc space group, as reported in our previous paper [32,33]. The morphology of the powder samples was observed using an ultra-high-resolution Field Emission Scanning Electron Microscope (FE-SEM) Hitachi SU7000.…”
Section: Materials Characterizationsupporting
confidence: 71%
“…Figure 3 b demonstrates the Mn emission band in transition metal cation Mn 2+ -doped perovskite NCs [ 16 ]. Moreover, the dopant in the crystal structure also leads to slightly improved electrochemical performances, such as discharge capacity and rate capability ( Figure 3 c) [ 58 , 59 ].…”
Section: Doping Strategiesmentioning
confidence: 99%
“…Adapted under a creative commons license from Ref. [ 58 ] ( (accessed on 14 September 2022)) Copyright 2021 by the authors.…”
Section: Figurementioning
confidence: 99%
“…Lithium-ion batteries (LIBs) have been dominating the market over the past three decades in portable devices. , However, the implementation of LIBs for large-scale applications is still facing issues due to limited reserves and the high price of lithium. , Additionally, Co is an invincible component of cathode used in high-capacity LIBs, which is also expensive, toxic, and scant in Earth’s crust. In the context of increasing demand for a substantial energy storage system, sodium-ion batteries (SIBs) are favorable substituents to LIBs considering notable characteristics such as Na abundance and wide availability around the globe. Both lithium and sodium have similar physicochemical properties; however, Na inherits a few more beneficial aspects than Li, like high desolvation and activation energies, which promote ion transport. , …”
Section: Introductionmentioning
confidence: 99%
“…5−7 Both lithium and sodium have similar physicochemical properties; however, Na inherits a few more beneficial aspects than Li, like high desolvation and activation energies, which promote ion transport. 8,9 In general, SIB intercalation hosts are categorized into different classes, such as layered transition metal oxides, polyanions, and Prussian blue analogues. 10,11 Among these, layered transition metal oxide cathodes are beneficial owing to their simple structure, easy synthesis, notable capacity, and choice of including a variety of transition elements in the cathode formulation.…”
Section: Introductionmentioning
confidence: 99%